1998
DOI: 10.1093/clinchem/44.6.1224
|View full text |Cite
|
Sign up to set email alerts
|

Remnant lipoprotein cholesterol and triglyceride reference ranges from the Framingham Heart Study

Abstract: Remnants of triglyceride-rich lipoproteins of both intestinal and liver origin are considered atherogenic, but they have been difficult to isolate and measure. An assay has been developed that allows the measurement of remnant-like particle cholesterol (RLP-C) and triglyceride (RLP-TG). RLP-C and RLP-TG concentrations were measured in >3000 fasting plasma samples obtained from participants in exam cycle 4 of the Framingham Offspring Study and stored at −80 °C. After exclusions, comparisons were made for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(30 citation statements)
references
References 40 publications
4
24
1
Order By: Relevance
“…They postulated that the increase in fasting RLP-C was related to insulin resistance and increased plasma triglyceride levels, whereas the increase in postprandial RLP-C could additionally be caused by lowered LPL activity in acromegaly. The levels of baseline RLP-C in our acromegalic patients are within the normal range found in normolipidaemic healthy Caucasian subjects (McNamara et al, 1998). However, recent data suggest that RLP-C levels in the high normal range may already have harmful effects.…”
Section: Discussionsupporting
confidence: 70%
“…They postulated that the increase in fasting RLP-C was related to insulin resistance and increased plasma triglyceride levels, whereas the increase in postprandial RLP-C could additionally be caused by lowered LPL activity in acromegaly. The levels of baseline RLP-C in our acromegalic patients are within the normal range found in normolipidaemic healthy Caucasian subjects (McNamara et al, 1998). However, recent data suggest that RLP-C levels in the high normal range may already have harmful effects.…”
Section: Discussionsupporting
confidence: 70%
“…atherogenic lipid profile in general and lower RLP-C levels in particular [mean RLP-C levels at baseline: 0·13 mmol L −1 (0·02); our study: 0·23 mmol L −1 (0·06)]. However, the RLP-C levels in our study were similar to those of women in the Framingham Heart Offspring study [22]. Several mechanisms are postulated to explain the effect of hormone replacement regimes on RLP particles.…”
Section: Discussioncontrasting
confidence: 44%
“…It has been demonstrated that insulin resistance or hypertriglyceridemia can increase small-dense LDL and remnant lipoproteins [29,30]. Some research has shown that high smalldense LDL or high remnant lipoprotein can induce arteriosclerosis and cardiovascular diseases [31,32].…”
Section: Discussionmentioning
confidence: 99%